Deradikalisasi ( Studi Atas Upaya Bnpt dalam Mencegah Munculnya Teroris di Lamongan) - Safii, Imam (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This paper is motivated by the war against terrorists in Indonesia with militaristic actions by taking action and enforcing the law, mobilizing the police apparatus especially Detachment 88 and carrying out executions of radical perpetrators. In fact the handling has not yet solved the problem of terrorism that occurred in Indonesia. It could even give birth to new terrorism from the families of Terrorist inmates - other terrorist inmates. So from this the need for handling a soft power approach is to strive for the de-radicalization of ex-terrorists who were convicted in the hope of preventing the emergence of new terrorists in the next era, as did the BNPT Terrorism Determination Agency in Lamongan. This program is intended for former terrorist convicts and families who are vulnerable to radical ideologies. Related to this, BNPT is collaborating with Yayasana Lingkar Perdamayan which also operates in the field of de-decalalization. This program is more concentrated on the economic independence of the families of prisoners of terrorism-ex-napiter. The program is concrete with a religious, psychological, socio-cultural, economic, legal, political and information technology approach.